Effect of different drying methods on phenolic content, antioxidant, antidiabetic, anti-obesity, and inhibition kinetic properties of selective green leafy vegetables - WAHYU HARYATI MASER; SUPATRA KARNJANAPRATUM; PASSAKORN KINGWASCHARAPONG; KARTHIKEYAN VENKATACHALAM; ALI MUHAMMED MOULA ALI; SRI CHARAN BINDU BAVISETTY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maser WH, Karnjanapratum S, Kingwascharapong P, Venkatachalam K, Ali AMM, Bavisetty SCB. 2023. Effect of different drying methods on phenolic content, antioxidant, antidiabetic, anti-obesity, and inhibition kinetic properties of selective green leafy vegetables. Biodiversitas 24: 4896-4909. The present study assessed the impact of dehydration drying, oven drying, and freeze drying on Total Phenolic Content (TPC), antioxidant activities (DPPH, metal chelating, and FRAP), and the inhibition activity of a-amylase, a-glucosidase, and lipase in selected green leafy vegetables, namely celery (Apium graveolens L.), coriander (Coriandrum sativum L.), parsley (Petroselinum crispum (Mill.) Fuss), and spring onion (Allium cepa L.). FTIR analysis was conducted to examine the functional groups, GC-MS was utilized to characterize the compounds, and a kinetic study of a-glucosidase inhibition was undertaken to assess its inhibitory mode as an antidiabetic agent. Freeze drying exhibited the highest extraction yield (17.89% to 26.15%). However, freeze-drying showed lower drying efficiency, TPC, and bioactivities. Oven drying showed the highest bioactivities, including antioxidant and enzyme inhibitory activities. Spring onion demonstrated the highest bioactivity with dehydration drying, particularly in a-glucosidase inhibitory activity. The results notified that oven drying can be highly suitable for green leafy vegetables with thinner structures, facilitating an efficient drying process. On the other hand, dehydration drying is better suited for thicker green leafy vegetables with the appropriate heat pump intensity. The results for bioactivities were aligned with the observed inhibition mechanism, functional groups, and bioactive compounds in the samples analyzed via FTIR and GC-MS analysis. Therefore, selecting the drying method for a specific sample should consider its unique characteristics to ensure optimal bioactivity.